Prototype Jemuran Pakaian Otomatis Menggunakan Arduino Berbasis Android - Sanji Muhammad Sidik; Hermawaty Hermawaty (LPPM STMIK AMIK BANDUNG, 2019)
Clothesline that is used in the community is still in the form of a manual so that the community must raise it directly. Peoplewho have more interests or who work may not have to raise clothes directly so they have to leave their more important work. Whentraveling or there are other jobs the community is still confused how to pick up clothesline with changing weather. From these problems,a prototype model of automatic clothesline was built using Android-based Arduino, this is to simplify and shorten the time in liftingclothesline or drying clothes when our weather changes. Having designed an automatic clothesline using Android-based Arduino. Inthis study, the Arduino UNO microcontroller functions as a data processing center obtained from the LDR sensor to detect light, usesa water sensor to detect rainwater and uses a DC motor to move the clothesline out / in, and uses the Bluetooth HC-05 module to movethe clothesline with Android. The test results show that this tool works well, when the device is turned on the sensor will check theweather outside whether the weather is sunny or rainy. When the weather is sunny or hot outside, the clothesline will automaticallycome out and if the weather outside is raining, the clothesline will automatically go inside. When the sensor does not function or hastrouble the automatic clothesline can be controlled via a smartphone that is connected to the Bluetooth HC-05 module.